The Lyα Sky as Observed by New Horizons at 57 au - G. Randall Gladstone; J. Michael Shull; Wayne R. Pryor; Jonathan Slavin; Joshua A. Kammer; Tracy M. Becker; Tod R. Lauer; Marc Postman; John R. Spencer; Joel Wm. Parker; Kurt D. Retherford; Michael A. Velez; et al. (The Astronomical Journal)
During 2023 September the Alice ultraviolet spectrograph on the New Horizons (NH) spacecraft was used to map diffuse Lyα emission over most of the sky, at a range of ∼56.9 au from the Sun. At that distance, models predict that the interplanetary medium Ly α emissions result from comparable amounts of resonant backscattering of the solar Ly α line by interstellar hydrogen atoms (H i ) passing through the solar system, in addition to an approximately isotropic background of ∼50 ± 20 R from the local interstellar medium (LISM). The NH observations show no strong correlations with nearby cloud structures of the LISM or with expected structures of the heliosphere, such as a hydrogen wall associated with the heliopause. To explain the relatively bright and uniform Ly α of the LISM, we propose that hot, young stars within the Local Hot Bubble shine on its interior walls, photoionizing H i atoms there. Recombination of these ions can account for the observed ∼50 R Ly α background, after amplification of the diffuse Ly α by resonant scattering, although sophisticated (i.e., 3D) radiative transfer models should be used to confirm this conjecture. Future observations of the diffuse Ly α , with instruments capable of resolving the line profile, could provide a new window on H i populations in the LISM and heliosphere. The NH Alice all-sky Ly α observations presented here may be repeated at some point in the future, if resources allow, and the two maps could be combined to provide a significant increase in angular resolution.